Connections of the laterodorsal tegmental nucleus with the habenular‐interpeduncular‐raphe system. Issue 18 (26th June 2019) - Bueno, Debora; Lima, Leandro B.; Souza, Rudieri; Gonçalves, Luciano; Leite, Fernanda; Souza, Stefani; Furigo, Isadora C.; Donato, Jose; Metzger, Martin
Abstract: The laterodorsal tegmental nucleus (LDTg) is a hindbrain cholinergic cell group thought to be involved in mechanisms of arousal and the control of midbrain dopamine cells. Nowadays, there is increasing evidence that LDTg is also engaged in mechanisms of anxiety/fear and promotion of emotional arousal under adverse conditions. Interestingly, LDTg appears to be connected with other regulators of aversive motivational states, including the lateral habenula (LHb), medial habenula (MHb), interpeduncular nucleus (IP), and median raphe nucleus (MnR). However, the circuitry between these structures has hitherto not been systematically investigated. Here, we placed injections of retrograde or anterograde tracers into LDTg, LHb, IP, and MnR. We also examined the transmitter phenotype of LDTg afferents to IP by combining retrograde tracing with immunofluorescence and in situ hybridization techniques. We found LHb inputs to LDTg mainly emerging from the medial division of the LHb (LHbM), which also receives axonal input from LDTg. The bidirectional connections between IP and LDTg displayed a lateralized organization, with LDTg inputs to IP being predominantly GABAergic or cholinergic and mainly directed to the contralateral IP. Moreover, we disclosed reciprocal LDTg connections with structures involved in the modulation of hippocampal theta rhythm including MnR, nucleus incertus, and supramammillary nucleus. Our findings indicate that the habenula is linked with LDTg either by direct reciprocal projections from/to LHbM or indirectly via the MHb‐IP axis, supporting a functional role of LDTg in the regulation of aversive behaviors, and further characterizing LHb as a master controller of ascending brainstem state‐setting modulatory projection systems. Abstract : As revealed by tract tracing methods, the habenula is linked with the laterodorsal tegmental nucleus (LDTg) either by direct reciprocal projections from/to LHbM or indirectly via the MHb‐IP axis, Moreover, LDTg and IP are closely associated to a distributed network of structures that modulate hippocampal theta activity (blue letters).